Gaiolas abertas: o feminino na contística de Augusta Faro - Ganzaroli, Hevellyn Cristine Rodrigues (2021)
This work aims to discuss the ways in which the feminine is represented in the scope of Goiás literature, based on the work of Augusta Faro. For that, we cut out two books of short stories by the author, which are A friagem (2001) and Boca Benta de Paixão (2007). Structured in three chapters, this research sought, through a diachronic route, to map what we call female brands in Brazilian and Goiás literature, in order to point out, in Brazilian literary historiography (BOSI, 2015; CANDIDO, 2000), moments when works of female authorship appeared and were occupying spaces of speech and artistic representation (ALMEIDA, 1996; AIRES, 1996). We also carried out a synthesis of the critical fortune of Augusta Faro, in order to demonstrate that the portrait of the feminine, as a whole, has not yet been sufficiently explored, both by the academy and by the specialized critic. We have also recovered the concept of a short story (PROPP, 2001) so that, based on this rescue, we can proceed to the analysis of four short stories taken from the two aforementioned works of the creator of Lua by the body, which make up the corpus of this work. We seek to show, through this study, that the feminine is portrayed, in the work of Augusta Faro, through resources and images that have the woman in transit, going from the cloister and the social and family enclosure to a state of greater freedom and assumption of her own voice. These are women who, albeit at a slow pace, claim, on the narrative level, their right to liberation from historical and social ties, tied to the patterns of patriarchalism (BEAUVOIR, 1967, 1970). We intend, through the thematic section of this work, to shed new light on the Goiás literature produced and themed by women.